SOURCE STUDIES OF ANCIENT GREECE (British Journal of Global Ecology and Sustainable Development, 2023)
The study of ancient Greece is one of the most important and interesting fields in the humanities. Ancient Greece is considered to be the birthplace of Western civilization, and its contributions to art, literature, philosophy, and politics continue to influence our world today. Source studies of ancient Greece are a vital part of understanding the culture and society of this fascinating civilization. In this article, we will explore the importance of source studies in ancient Greek history, and the various types of sources that are available for study.